2018
DOI: 10.3390/antiox7100142
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Arabidopsis thaliana TRXo Isoforms Bind an Iron–Sulfur Cluster and Reduce NFU Proteins In Vitro

Abstract: In plants, the mitochondrial thioredoxin (TRX) system generally comprises only one or two isoforms belonging to the TRX h or o classes, being less well developed compared to the numerous isoforms found in chloroplasts. Unlike most other plant species, Arabidopsis thaliana possesses two TRXo isoforms whose physiological functions remain unclear. Here, we performed a structure–function analysis to unravel the respective properties of the duplicated TRXo1 and TRXo2 isoforms. Surprisingly, when expressed in Escher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Sequence analysis and structural representation of plant TRXs. ( a ) Multiple sequence alignment of structurally solved plant TRX isoforms was performed with ESPript (, [42]) using Chlamydomonas reinhardtii (Cr) TRX h1 (Protein Data Bank (PDB) ID: 1EP7, [19]) and TRX m (PDB ID: 1DBY, [25]), Arabidopsis thaliana (At) TRX h1 (PDB ID: 1XFL, [26]), TRX o1 (PDB ID: 6G61, [27]), and TRX o2 (PDB ID: 6G62, [27], Hordeum vulgare (Hv) TRX h1 (PDB ID: 2VM1, [28]) and TRX h2 (PDB ID: 2IWT, [28]); Populus trichocarpa (Pt) TRX h1 (PDB ID: 1TI3, [29]) and TRX h4 (PDB ID: 3D21, [30]), and Spinacia oleracea (So) TRX f (PDB ID: 1F9M, [31]) and TRX m (PDB ID: 1FB0, [31]). Conserved residues are highlighted in white on red boxes, whereas residues with similar physicochemical properties are written in black on yellow boxes.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis and structural representation of plant TRXs. ( a ) Multiple sequence alignment of structurally solved plant TRX isoforms was performed with ESPript (, [42]) using Chlamydomonas reinhardtii (Cr) TRX h1 (Protein Data Bank (PDB) ID: 1EP7, [19]) and TRX m (PDB ID: 1DBY, [25]), Arabidopsis thaliana (At) TRX h1 (PDB ID: 1XFL, [26]), TRX o1 (PDB ID: 6G61, [27]), and TRX o2 (PDB ID: 6G62, [27], Hordeum vulgare (Hv) TRX h1 (PDB ID: 2VM1, [28]) and TRX h2 (PDB ID: 2IWT, [28]); Populus trichocarpa (Pt) TRX h1 (PDB ID: 1TI3, [29]) and TRX h4 (PDB ID: 3D21, [30]), and Spinacia oleracea (So) TRX f (PDB ID: 1F9M, [31]) and TRX m (PDB ID: 1FB0, [31]). Conserved residues are highlighted in white on red boxes, whereas residues with similar physicochemical properties are written in black on yellow boxes.…”
Section: Figurementioning
confidence: 99%
“…Although plant TRXs have been thoroughly characterized at the functional level, structural data are still limited to only 11 three-dimensional structures available so far [4]. This list includes TRX h1 and m from Chlamydomonas reinhardtii (CrTRXh1, [19]; CrTRXm, [25], TRX h1, o1, and o2 from Arabidopsis thaliana (AtTRXh1, [26]; AtTRXo1 and AtTRXo2, [27]), TRX h1 and h2 from Hordeum vulgare (HvTRXh1 and HvTRXh2, [28]), TRX h1 and h4 from Populus trichocarpa (PtTRXh1, [29]; PtTRX h4, [30]), and TRX f and m from Spinacia oleracea (SoTRXf and SoTRXm, [31]). In all cases, TRXs structures were solved in the oxidized form, except for plastidial SoTRXm, and cytoplasmic HvTRXh2 for which the 3D structure of the reduced forms is available.…”
Section: Introductionmentioning
confidence: 99%
“…After glutathionylation, disulfide bonds may be formed with another protein thiol and both forms can be reversed by GSH, GRX, or TRX as it has been described in animal systems (Beer et al, 2004) (Figure 1). In plants, several TRXs h present a de-glutathionylation activity although with a lower efficiency than GRXs as demonstrated for Arabidopsis cytosolic glyceraldehyde-3-phosphate dehydrogenase (Bedhomme et al, 2012), explaining the absence of GRX in plant mitochondria with de-glutathionylation activity (Zannini et al, 2018). In fact, mitochondrial TRX h undergoes glutationylation and the thiolation alters its redox potential as identified by MS (Gelhaye et al, 2004).…”
Section: S-glutathionylationmentioning
confidence: 99%
“…The presence of TRX and NADPH-TRX reductase (NTR) activities was initially detected in plant mitochondria ( Marcus et al, 1991 ; Konrad et al, 1996 ), but the native proteins were not identified and characterized. Laloi et al (2001) identified AtTRX-o1 and AtTRX-o2 genes encoding two TRX o isoforms in Arabidopsis, being TRX o 1 unequivocally present in mitochondria whereas the TRX o 2 cellular location is still not clear ( Zannini et al, 2018 ). Later on, Gelhaye et al (2004) found that poplar mitochondria also contain a TRX isoform belonging to the TRX h type (PtTRX h 2), earlier identified in the cytosol.…”
Section: Mitochondrial Targets Of S-oxidation S-glutathionylation Smentioning
confidence: 99%
See 1 more Smart Citation